Wakaf Abdan Dalam Pendidikan Islam - Ainur Rofiq, Ahmad; Makhrus Ali, Muhammad; Alfarisi, Salman (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2023)
Management of productive waqf in Indonesia has received legal protection. Through Law no. 41 of 2004 concerning waqf, actually waqf management is directed at the productive sector. Pondok Modern Darussalam Gontor, East Java is one of the relatively successful nazhirs. Since the beginning of its development, Pondok Modern Darussalam Gontor has called itself a "waqf Islamic boarding school". This Islamic boarding school is a Trimurti waqf, which Trimurti officially handed over on October 12 1958 to the community represented by the Pondok Modern Darussalam Gontor Waqf Board. Pondok Modern Darussalam Gontor is considered successful in utilizing its productive waqf proceeds to finance itself and therefore can be used as a model for the development of waqf-based educational institutions. This type of research is a literature study which aims to analyze several findings from the Al Quran, Hadith Books and journals. This research uses a qualitative method with a qualitative descriptive design by analyzing, identifying and exploring the findings from previous research results. The objects of this research are the Koran, Hadith books and journals. The results of this research are that Pondok Modern Darussalam Gontor accommodates self-waqf with the aim of ensuring the survival of the Pondok and views it as part of the service waqf, because basically the practice of such waqf has been carried out by the community.